Fisiologi Penglihatan Ikan Selar (Selar crumenophthalmus) dan Aplikasinya dalam Proses Penangkapan Ikan dengan Mini Purse Seine - Aristi Dian Purnama Fitri (Universitas Gadjah Mada, 2006)
Research about visual physiology of Bigeye as a group of tropical fish was still limited. The aim of this research was to know visual physiology of Bigeye, and the application in arrest process of fish catch of mini purse seine. Retina of fish samples with the total length of size 205-260 mm were analyzed by histological observation and calculation of formula in order to know visual acuity and maximum sighting distance, and then application process at mini purse seine to know getting away model of appliance coverage catch. Visual acuity of Bigeye ranged from 0.09 to 0.1. The object was net of mini purse seine diameter of 1.90-22.00 mm and maximum sighting distance of 0.39-7.17 m. Get away time of Bigeye were 7.45 sec; 6.45 sec; and 5.70 sec at condition of sustained speed; prolonged speed; and burst speed, respectively. Appliance time of mini purse seine to circle of perfection was 290.82 second.